The association of length of hospital stay with readmission after elective pancreatic resection. Issue 1 (27th June 2018) - Mazmudar, Aditya; Castle, Joshua; Yang, Anthony D.; Bentrem, David J.
Abstract : Objective: The aim of this study was to identify if prolonged length of hospital stay was protective for certain post‐discharge complications requiring readmission after pancreatectomy. Methods: Patients undergoing elective pancreatectomy from 2012 to 2013 were identified in the American College of Surgeons National Surgical Quality Improvement Program (ACS‐NSQIP). Multivariate regression analyses were conducted to elucidate the association of length of hospital stay (LOS), in‐hospital complications, and post‐discharge complications with 30‐day hospital readmission. Results: Mean LOS for the readmitted versus not readmitted cohort was 9.01 and 10.36, respectively ( P  < 0.001). Approximately half of hospital readmissions occur within 7 days of discharge from the hospital. The readmission rate (after hospital discharge) for patients with any in‐hospital complication was 13.2%. On the other hand, the readmission rate for patients with any post‐discharge complication was 70.8%. Readmission rates were above 85% for patients with the following post‐discharge complications: organ/space surgical site infection (SSI), pneumonia, ventilator dependence greater than 48   h, progressive renal insufficiency, sepsis, and septic shock. In a multivariate logistic regression model, prolonged LOS reduced the odds of any post‐discharge complication requiring readmission (OR   =   0.68, P  =   0.01). Specifically, prolonged LOS reduced the odds of a post‐discharge organ/space SSI requiring readmission (OR   =   0.72, P  =   0.02). Conclusion: Readmission after pancreatectomy primarily occurs due to a new post‐discharge event. Furthermore, increased LOS is protective for readmission for post‐pancreatectomy complications, particularly those due to post‐discharge organ space SSIs. Our findings suggest that solely focusing on reducing LOS in pancreatectomy may lead to the unintended consequence of increasing readmission rates.